PERLINDUNGAN HUKUM TERHADAP KREDITUR ATAS WANPRESTASI DEBITUR PADA PERJANJIAN KREDIT DENGAN JAMINAN HAK TANGGUNGAN - Yulia Risa (Fakultas Hukum Universitas Tamansiswa Padang, 2017)
In the crediting process, it is often the case that the creditor is disadvantaged when the debtor has defaulted, so that a legal rule is required in the implementation of the imposition of the Mortgage Rights contained in a credit agreement, which aims to provide certainty and legal protection for the parties concerned, based on the results the explanation of Article 10 of Law No. 4/1996 concerning the Right of Million of Land and Land Related Item, it is explained that the agreement which creates the legal relationship of these debts can be made in writing either in the form of deed under the hand or deed authentic, depending on the legal provisions governing the material of the agreement. the right of the creditor to recover the receivable when the debtor is default on the credit agreement with the authentic deed. This authentic deed has advantages that can be requested Grosse Deed of Recognition Debt that has the power eksekutorial and become the basis for the execution if the debtor injures the promise.